2002
DOI: 10.4049/jimmunol.169.12.6883
|View full text |Cite
|
Sign up to set email alerts
|

TNFR-Associated Factor-3 Is Associated With BAFF-R and Negatively Regulates BAFF-R-Mediated NF-κB Activation and IL-10 Production

Abstract: TALL-1 is a member of the TNF family that is critically involved in B cell survival, maturation, and progression of lupus-like autoimmune diseases. TALL-1 has three receptors, including BCMA, TACI, and BAFF-R, which are mostly expressed by B lymphocytes. Gene knockout studies have indicated that BAFF-R is the major stimulatory receptor for TALL-1 signaling and is required for normal B cell development. The intracellular signaling mechanisms of BAFF-R are not known. In this report, we attempted to identify BAFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 61 publications
6
128
0
Order By: Relevance
“…Since then, several studies reported similar effects of TRAF3 on the NF-B signaling of the LT␤R (41), OX40 (42), BAFF (43), LMP (26,27), and CD40 (44). Until it was demonstrated that TRAF2 and TRAF3 do not interfere with each other's CD40 binding (39), this TRAF3 function was attributed to competition between TRAF3 and TRAF2͞5 for their common receptor-binding site (7,26,27,43,44). A common problem of these studies is that they did not account for the existence of the two NF-B-signaling pathways and measured only molecular events that characterize the canonical NF-B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies reported similar effects of TRAF3 on the NF-B signaling of the LT␤R (41), OX40 (42), BAFF (43), LMP (26,27), and CD40 (44). Until it was demonstrated that TRAF2 and TRAF3 do not interfere with each other's CD40 binding (39), this TRAF3 function was attributed to competition between TRAF3 and TRAF2͞5 for their common receptor-binding site (7,26,27,43,44). A common problem of these studies is that they did not account for the existence of the two NF-B-signaling pathways and measured only molecular events that characterize the canonical NF-B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence indicates that BAFF-R interacts with TRAF3, but not other members of the TRAF family in B cells [56,58]. A major outcome of BAFF-R stimulation is the activation of the alternative NF-κB (NF-κB2) pathway, which is known to be essential for the survival of primary B cells [56].…”
Section: Receptors For Baff and Aprilmentioning
confidence: 99%
“…In human, TACI mutations have been associated with common variable immunodeficiency [56]. Interaction between TACI and TRAF3 has been demonstrated in the B lymphoma cell line BJAB [58]. Overexpressed TACI co-immunoprecipitates with TRAF2, TRAF5 and TRAF6 in 293 epithelial cells [63].…”
Section: Receptors For Baff and Aprilmentioning
confidence: 99%
“…Instead, EC1 contains several genes whose products attenuate activation of NFkB. These include IkB-a and -e, which both directly block NFkB entry to the nucleus; TNFAIP3, BIRC3 and IER3, which encode distinct proteins annotated as attenuating various steps in the TNF signaling pathway downstream of TRAF [22][23][24][25] . We confirmed IL18 induction of many transcript changes by quantitative PCR using KG1 RNA samples and RNA samples prepared from whole human blood treated with recombinant IL18 (Table 1).…”
Section: Il18-induced Nfjb Bindingmentioning
confidence: 99%
“…Preparation of probe and target hybridization-10 mg of total RNA and the SuperScript Choice System for cDNA Synthesis (Gibco BRL) were used to synthesize double-stranded cDNA. The synthesis was carried out according to Affymetrix protocol, which requires T7-(dT) 24 oligomer primers (GENSET) in place of the oligo (dT) or random primers provided with the kit and which calls for incubations at 421C during the temperature adjustment and first-strand synthesis steps. The resulting cDNA was cleaned with Phase Lock Gel Light 2 ml tubes (Eppendorf), and the pellet was resuspended in 12 ml of DEPC-H 2 O.…”
Section: Experimental Designmentioning
confidence: 99%